OTOMASI PID TUNING UNTUK OPTIMASI KONTROL QUADCOPTER MENGGUNAKAN METODE HARMONY SEARCH - Wimmy Hartawan (Universitas Pahlawan Tuanku Tambusai, 2021)
The search system intelligent tuning value on the Quadcopter control method the topics the one of research that continues to be developed, starting from conventional control systems to intelligent control systems. The methods of control commonly today used include PID control. The automatic control system is handle to able several disturbances from internal and external factors. Internal factors can be caused from vibration than perfect less and actuator devices. External factors form the changes in the wind direction and speed, waves and wind current speed resulting is changes in the orientation on direction from the quadcopter. External factors that are disturbances of difficult to predict and relatively in change non-linear. The HS (Harmony Search) algorithm is one of the optimization algorithms can be used decision maker system, which a metaheuristic method inspired by compositions of jazz. The Harmony Search algorithm has initialization step a harmony memory. This stage a advantage of being to able simultaneously find several combinations of points from the initial route that be obtained from the given initial route. In the Harmony Search method, it by analogy can be explained, when is improvising a musical instrument player, there are can be done three things that, namely: playing notes that are composition in the song already available, playing notes that have in harmony accordance with the song composition (pitch adjustment) and playing notes randomly. The results of the PID tuning simulation research using Harmony Search found constants Kp, Ki and Kd with the smallest rise time and overshoot for all angles. At the corner it is found that Kp is worth 0.176, Ki is worth 0.008 and Kd is 0.098.